Loss versus gain: integrating technology and message framing in promoting proper hand washing among grade 1 pupils - Analin B, (Universiti Kebangsaan Malaysia, 2011)
One of the major functions of nurses is to promote health and wellness of individuals both healthy and ill. Promoting proper hand washing is the most basic infection-control measure a nurse can assume to attain this goal. Individuals become more susceptible to diseases without proper practice and sufficient understanding of this skill. It is a challenge for nurses to encourage the people to be compliant in making hand washing a necessary part in the maintenance or improvement of their health. This is especially true for school-aged children, who are constantly exposed to the environment and thus to bacterial and infectious agents, are at a higher risk. Technology has widened the dissemination of knowledge. Audio-Visual Presentations (AVP) has made education and learning more easily facilitated. Education involves giving information to improve knowledge about a certain concept and Message Framing is one method. The study combined the two strategies in promoting hand washing.The objective of this study is to determine which type of message framing through an AVP: positive (shows benefits and gains) or negative (shows risks and losses), is more effective in promoting proper hand washing among Grade 1 pupils. The researchers included 72 grade 1 pupils from a public elementary school to participate in the study through convenience and cluster sampling. The data was gathered through a pre-test and post-test method. In the analysis, the total average scores of the posttest of each group, positive message framing and negative message framing, was used to determine which type of message framing through an AVP is more effective in teaching and promoting proper hand washing. Further, the paired t-test method was used to determine if there is a significant increase in the average scores of all the students from pretest to posttest to see if there is an improvement in the knowledge and beliefs of students regarding proper hand washing. A 17-item Hand Hygiene Questionnaire served as a pretest and posttest to gather data.The findings showed that positive message framing through an AVP is more effective in promoting proper hand washing among Grade 1 pupils. Positive message framing group showed a higher posttest average and indicates better understanding and improved knowledge about proper hand washing.This result of this study will help nurses as well as teachers and other health care professionals in applying a new strategy in promoting health and wellness among their clients.